Attitudes of 15–16-Year-Old Pupils with a Sufficient Activity Level Towards the Physical Education Teacher and Their Behaviour (Baltic Journal of Sport and Health Sciences, 2017)
Background. As our society is subject to changes, knowledge about the learners’ attitudes towards a physical education teacher, their behaviour and characteristics can help to more effectively address the problems of physical education at school. The research hypothesis was raised in this article as follows: attitudes of 15–16-year-old pupils with a sufficient activity level towards a physical education teacher and their behaviour will differ with respect to gender: the male pupils’ approach will be more positive than that of female pupils. Research aim was to investigate the attitudes of 15–16-year-old pupils with a sufficient activity level towards a physical education teacher and their behaviour.Methods. The survey was conducted during physical education classes in Kaunas secondary schools in spring, 2015. The questionnaire survey was carried out. Questionnaire data of 300 sufficiently physically active pupils (150 boys and 150 girls) were analysed.Results. Both boys and girls indicated good knowledge of the subject, friendliness, communication with the group, taking into account pupils’ opinions as the most appealing characteristics of the physical education teacher. Both  genders  considered  that  the  most  unfavourable  teacher  characteristics  were  insisting  on  meeting  physical standards, non-involvement in physical activities together with pupils in the classroom and disregarding pupils’ needs and wishes. More girls than boys (p < .05) did not appreciate the teacher’s non-communication with pupils, lack of dedication and making offensive comments.Conclusions. Both boys and girls pointed out that the most appealing traits of the physical education teacher’s characteristics were good knowledge of the subject, friendliness, communication with the group and taking into account pupils’ opinions. Girls appeared to be more demanding to the physical education teacher’s behaviour than boys.Keywords:  attitude to physical education teacher, pupils, teacher’s behaviour.